2018
DOI: 10.1016/j.neurobiolaging.2018.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Muscle strength and size are associated with motor unit connectivity in aged mice

Abstract: In older adults, the loss of muscle strength (dynapenia) and the loss of muscle mass (sarcopenia) are important contributors to the loss of physical function. We sought to investigate dynapenia, sarcopenia, and the loss of motor unit function in aging mice. C57BL/6J mice were analyzed with cross-sectional (males: 3 vs. 27 months; males and females: 8 vs. 12 vs. 20 months) and longitudinal studies (males: 10–25 months) using in vivo electrophysiological measures of motor unit connectivity (triceps surae compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 48 publications
6
70
1
Order By: Relevance
“…Additionally, a loss of motoneurons, neuromuscular remodelling, denervation and fibre‐type switch may also contribute to reduced numbers of muscle fibres and the overall muscle mass …”
Section: Sarcopeniamentioning
confidence: 99%
“…Additionally, a loss of motoneurons, neuromuscular remodelling, denervation and fibre‐type switch may also contribute to reduced numbers of muscle fibres and the overall muscle mass …”
Section: Sarcopeniamentioning
confidence: 99%
“…While protein homeostasis within the skeletal muscle largely affects its structure and function, further studies should also investigate how changes in protein homeostasis in skeletal muscle might affect the communication between the muscular and nervous systems,, i.e., the neuromuscular junction. Loss of innervation of the skeletal muscle is also a phenotype of ageing and previous studies have shown that the loss of neuronal connection with the muscle, by experimental model of denervation, is associated with impaired motor function and muscle strength . Denervation‐evoked impairment of muscle function will result in further muscle disuse, which may exacerbate muscle atrophy with age .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 10-15 month-old mice can be considered as middle-aged, during which time senescence processes and reproductive decline begin to occur [23,24]. With aging, gains in body mass [25][26][27][28] and decreases in locomotor activity are frequently observed [25,[27][28][29][30][31] but see [32].…”
Section: Introductionmentioning
confidence: 99%